Features of electrical activity of human brain during prolonged staying in Antarctica - V. I. Sukhorukov; L. P. Zabrodina (Ukrainian Antarctic Journal, 2012)
The study of winterers’ electrical brain activity during prolonged staying in Antarctica has been held. Complicated dynamic intersystem structural and functional reorganization of brain activity, indicating the development of strain in adaptive brain mechanisms from the first wintering months, has been shown. In the second half of the wintering activation of somnohenius mechanisms in brain activity regulation and decreasing of functional brain activity has been observed.